보쉬-분스트라-샤프 시신경위축 증후군의 안과적 이상 - 이동준(Dong Jun Lee), 양승안(Seung Ahn Yang), 전종근(Chong Kun Cheon), 김수진(Su Jin Kim) (Daihan angwa haghoi jabji, 2025)
목적: 유전적으로 확진된 보쉬-분스트라-샤프 시신경위축 증후군 환아 1예를 보고하고자 한다. 증례요약: 만 4세 남아가 우안의 내편위 및 눈떨림을 주소로 내원하였다. 최대교정시력은 우안 0.15, 좌안 0.1로 측정되었고, 현성잠복안진이 확인되었으며, 프리즘교대가림검사에서 근거리 및 원거리 모두 16프리즘디옵터의 내편위가 관찰되었다. 안저검사에서 양측 시신경유두가 창백하였고, 빛간섭단층촬영에서 망막중심오목형성저하 및 시신경섬유층과 신경절세포층-속얼기층의 두께 감소가확인되었다. 섬광 시유발전위검사에서 P100 지연을 보였으나, 망막전위도검사 및 뇌자기공명검사에서는 특이 소견이 관찰되지 않았다. 한국형 영유아발달검사에서 미세근육 77퍼센트, 언어 84퍼센트의 발달 수준으로 평가되어 유전자검사를 의뢰하여 전장 엑솜 분석시행하였고, NR2F1 유전자의 c.208_211del:p.(Lys70Alafs*48)이 확인되어 보쉬-분스트라-샤프 시신경위축 증후군으로 확진하였다. 결론: 눈떨림 환자에서 시신경위축을 동반하는 경우 보쉬-분스트라-샤프 시신경위축 증후군을 감별하고, 발달지연 등 동반되는 질환에 대한 조기 진단 및 치료가 필요할 것이다. Purpose: We present a case of a patient with genetically confirmed Bosch–Boonstra–Schaaf optic atrophy syndrome (BBSOAS). Case Summary: A 4-year-old male patient attended the ophthalmologic clinic with complaints of esodeviation in his right eye and nystagmus. His best-corrected visual acuity was 0.15 in the right eye and 0.1 in the left eye. The prism and alternate cover test indicated 16 prism diopters of esotropia for both distance and near, and manifest latent nystagmus was noted. Fundus examination showed pale optic discs in both eyes, and optical coherence tomography revealed reduced central retinal thickness and thinning of the retinal nerve fiber layer, ganglion cell layer, and inner plexiform layer. Flash visual evoked potential tests indicated a delayed P100 wave, while electroretinography showed no notable findings. Brain magnetic resonance imaging showed no distinctive abnormalities. Developmental assessment using a Korean developmental scale fine motor and language skill scores of 77% and 84%, respectively. Exome sequencing identified a mutation (c.208_211del:p.(Lys70Alafs*48)) in the NR2F1 gene, confirming the diagnosis of BBSOAS. Conclusions: BBSOAS should be considered in the differential diagnosis of patients with optic atrophy and nystagmus. Early diagnosis and recognition of developmental delays are important for optimal management. KCI Citation Count: 0